EIGHT ASPECT DESIGNS OF BOARDING SCHOOL BASED ON PREFERENCE IN NEW NORMAL ERA OF COVID-19, KENDARI CITY AND BANDUNG AS CASE STUDIES - Dui Buana Mustakima; Hanson E.Kusuma (Ide dan Dialog Desain Indonesia (Idealog), 2022)
The development of boarding houses need to be supported by certain guidelines which have abilities to face the new normal era. The guidelines need to consider people' perspectives as users directly experienced this situation. However, the guidelines which is considering new normal are still limited. The purpose of this research is to know the preferences of people toward the ideal boarding house. This research was done quantitatively with grounded theory approach which is explorative. The data collection was done by sharing open-ended online questionnaires. The questionnaires were shared freely (non-random sampling). There were 158 respondents filled, 128 of the are respondents living in kendari and others are from Bandung. The data collected were analyzed using content analysis. In this analysis was done with two steps called open coding and selective coding. Results showed that there are eight aspects which become preferences of boarding houses in new normal era. Health is the new and influential aspect aspesct. This research is expected to be a part of consideration of government and private sectors in making policy and desgning relating to boarding houses more anticipatory. Particularly boarding houses located in Kendari and Bandung city. Keywords : boarding house, new normal, Covid-19, design criteria